The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/es0255711
|View full text |Cite
|
Sign up to set email alerts
|

Field Demonstration of Successful Bioaugmentation To Achieve Dechlorination of Tetrachloroethene To Ethene

Abstract: A laboratory microcosm study and a pilot scale field test were conducted to evaluate biostimulation and bioaugmentation to dechlorinate tetrachloroethene (PCE) to ethene at Kelly Air Force Base. The site groundwater contained about 1 mg/L of PCE and lower amounts of trichloroethene (TCE) and cis-1,2-dichloroethene (cDCE). Laboratory microcosms inoculated with soil and groundwater from the site exhibited partial dechlorination of TCE to cDCE when amended with lactate or methanol. Following the addition of a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
329
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(338 citation statements)
references
References 19 publications
5
329
0
3
Order By: Relevance
“…Natural and enhanced degradation of chlorinated ethenes in high permeability deposits (aquifers) is well known Major et al, 2002;Scheutz et al, 2008). In low permeability media, such as clay tills, little is known about how degradation by reductive dechlorination distributes between preferential flow paths such as sand lenses and fractures and the clay till matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Natural and enhanced degradation of chlorinated ethenes in high permeability deposits (aquifers) is well known Major et al, 2002;Scheutz et al, 2008). In low permeability media, such as clay tills, little is known about how degradation by reductive dechlorination distributes between preferential flow paths such as sand lenses and fractures and the clay till matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Several microbial groups carry out respiratory reductive dechlorination 1 , but one genus, Dehalococcoides, seems particularly adapted to a unique niche, and the bacteria are only known to use chloroorganics as electron acceptors and hydrogen as an electron donor for growth. Several studies have now shown successful application of Dehalococcoides-containing cultures for in situ remediation of contaminated sites 2,3 . The recently described genome sequence of D. ethenogenes, strain 195 (ref.…”
mentioning
confidence: 99%
“…Consortia containing Dehalococcoides organisms have been successfully applied at field sites where the intrinsic microbiology was insufficient to sustain acceptable degradation rates (27 ). Knowing the key players (i.e., Dehalococcoides ) and understanding the microorganisms' ecology were critical for successful technology implementation.…”
Section: Complete Biodegradation Of Pcementioning
confidence: 99%
“…Perhaps they seek a single "magic bullet". Up to now, direct, incontrovertible proof has been scarce, but it is beginning to emerge (27).…”
Section: Where Are the Benefits And Roadblocks?mentioning
confidence: 99%